Influence of Iodide Ions Concentration on the Stability of 1-Ethyl-3-methylimidazolium Tetrafluoroborate | Molybdenum Carbide Derived Carbon Electrode Interface. Issue 6 (25th March 2017) - Kruusma, Jaanus; Tõnisoo, Arvo; Pärna, Rainer; Nõmmiste, Ergo; Vahtrus, Mikk; Siinor, Liis; Tallo, Indrek; Romann, Tavo; Lust, Enn
Abstract : Influence of the iodide ions adsorption on the in situ measured X-ray photoelectron spectra of C 1s, N 1s, B 1s, F 1s and I 3d photoelectrons, indicating the changes in the chemical composition taking place at the carbon (C) | 1-ethyl-3-methylimidazolium tetrafluoroborate (EMImBF4 ) + 1-ethyl-3-methylimidazolium iodide mixed ionic liquids interface, has been studied. Simultaneously, the stability of the formed C electrode | ionic liquid interface has been analyzed electrochemically. Electroreduction of the BF4 − anion seems to start at less negative potential than the 1-ethyl-3-methylimidazolium (EMIm + ) cation. Addition of the I − ions to the EMImBF4 initiates the electrochemical processes at C electrode at lower negative or positive potentials. However, intensity of the electrochemical reduction of EMIm + cation was suppressed. The experiments, performed in the vacuum conditions, indicated that slow faradaic oxidation processes started already at E ≥ 1.0 V (vs. Ag/AgCl in EMImBF4 ). Our investigations clearly show that the formed passivating layer at the carbon electrode is unstable and decomposes slowly producing gaseous products. Based on the analysis of results collected the electrode materials for electrochemical double layer capacitors should be tested in the vacuum conditions in order to detect the early start of very slow faradaic processes producing gaseous products.